Incidental radiologic findings in breast cancer patients who undergo staging prior to neo‐adjuvant chemotherapy. Issue 4 (25th January 2021) - Srour, Marissa K.; Lee, Minna; Wolcott‐Sapp, Sarah; Luu, Michael; Chung, Alice; Giuliano, Armando E.; Amersi, Farin
Abstract: NCCN guidelines discourage the use of staging imaging for newly diagnosed patients with early breast cancer (BC). When performed, incidental radiologic findings of uncertain significance are often encountered. The purpose of this study was to compare incidental findings seen on staging imaging with distant recurrence in patients undergoing neo‐adjuvant chemotherapy (NAC). 396 patients with BC who had NAC from 2008 to 2016 were identified from a prospectively maintained data base. Staging imaging was reviewed. Of 396 patients with BC treated with NAC, patients with a positive PET/CT for metastatic disease ( n = 36, 9.1%), those that did not undergo staging imaging ( n = 49, 12.4%), or those that did not have a reported incidental finding ( n = 49, 12.4%) were excluded from analysis. Of the 262 patients who met criteria, mean age was 50 years (range: 26–88). 201 (76.7%) patients had stage I‐II cancer, and 61 (23.3%) patients had stage III cancer. Overall, 146 (55.7%) patients had an incidental finding on imaging. 90 (34.4%) patients had one finding, 42 (16.0%) patients had two, and 14 (5.3%) patients had three or more findings. The majority of incidental findings were seen in the ovary/uterus (29.7%), followed by lung (18.4%), liver (10.3%), and bone (9.0%). 5 (3.4%) patients had additional imaging performed. At mean follow‐up of 3.7 years (range: 0.7–10.8), 43 (15.6%) patients had a distant recurrence. Of these patients, only 5 (1.9%) patients had distant metastasis in the same organ that was initially thought to be an incidental finding. Our results suggest that breast cancer patients with incidental findings on preoperative staging imaging are unlikely to be indicative of sites for future metastasis.